2016
DOI: 10.1016/j.mambio.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of the water opossum Chironectes minimus in Atlantic Forest streams

Abstract: Spatial ecology of the water opossum Chironectes minimus in Atlantic Forest streams.Mammalian Biology http://dx. ABSTRACTThe water opossum Chironectes minimus is the world's only semi-aquatic marsupial. It is considered rare, and it is reported on several regional conservation lists of species as either endangered or data deficient. Given its uniqueness and the poor knowledge of its ecology, we aimed to investigate home range size and overlap and habitat selection of the water opossum in Atlantic Forest stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Here, records were more frequent in the dry season, but we could not determine the sex of the filmed individuals. Considering that the home length of C. minimus may vary between 0.8 and 9.6 km but few individuals have home lengths larger than 6.7 km (Fernandez et al 2015, Leite et al 2016, it is likely that the records reported herein represent at least two individuals.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Here, records were more frequent in the dry season, but we could not determine the sex of the filmed individuals. Considering that the home length of C. minimus may vary between 0.8 and 9.6 km but few individuals have home lengths larger than 6.7 km (Fernandez et al 2015, Leite et al 2016, it is likely that the records reported herein represent at least two individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Vehicle collision rate seems to be low for C. minimus even when compared with other semi-aquatic mammals such as the capybara (Hydrochoerus hydrochaeris) and the Neotropical otter (Lontra longicaudis) (Coelho et al 2008, Huijser et al 2013, Magioli et al 2019. A plausible explanation for the rarity of roadkills is that C. minimus seems to never leave watercourses during its daily movements (Leite et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At local spatial scale, the water opossum is potentially threatened by deforestation of riverine vegetation, contamination and deterioration of freshwater ecosystems (Pérez-Hernandez et al 2016). In Atlantic Forest, C. minimus has been described as highly sensitive to the degradation of riparian forest and riverine vegetation, preferring well preserved habitats such as streams and rivers with stony substrate, clear and fast-running water associated with a highly preserved riparian forest (Handley 1976, Galliez et al 2009, Palmeirim et al 2014, Leite et al 2016). However, the water opossum also seems to be able to occur in degraded habitats, with few studies showing that this marsupial is found in degraded riverine forests.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this behavioral expression largely determines animal fitness as well as its ecological roles in the ecosystem, considering that the environment is highly dynamic in terms of and resource availability [4,5]. Spatial behavior, therefore, may be strongly correlated to morphological (body mass), physiological (metabolic rate), ecological (intra-and interspecific interactions, diet and foraging strategies), social, and environmental factors [6,7]. Information on spatial behavior in wild animals is difficult to obtain (and particularly for cryptic species), but is important for understanding their home range, social interactions, mating systems and foraging strategies [8].…”
Section: Introductionmentioning
confidence: 99%